2023
DOI: 10.3847/2041-8213/acb934
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamical Simulations of Black Hole Binary Formation in AGN Disks

Abstract: We study close encounters between two single black holes (BHs) embedded in an AGN disk using a series of global 2D hydrodynamics simulations. We find that when the disk density is sufficiently high, bound BH binaries can be formed by the collision of their circum-single disks. Our analysis demonstrates that, after a BH pair passes the pericenter of their relative trajectory, post-collision gas drag may slow down the BHs, possibly forcing the two BHs to stay tightly bound. A binary formed by a close encounter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 66 publications
(148 reference statements)
0
7
0
Order By: Relevance
“…Simulations have shown that during their encounters, disk-embedded binaries can become bound after their separation reach of order J. Li et al 2022aJ. Li et al , 2023, which means their capture impact parameter is effectively ∼R H .…”
Section: Binary Capture Timescalementioning
confidence: 99%
“…Simulations have shown that during their encounters, disk-embedded binaries can become bound after their separation reach of order J. Li et al 2022aJ. Li et al , 2023, which means their capture impact parameter is effectively ∼R H .…”
Section: Binary Capture Timescalementioning
confidence: 99%
“…The unusual disk environment causes stars to accrete and grow in mass much more rapidly than elsewhere in the interstellar medium, changing the stars' structure, allowing them to reach much higher masses, and making BH remnants a more common outcome upon their death (Cantiello et al 2021;Dittmann et al 2021;Jermyn et al 2021). Once trapped in the AGN disk, BHs can go through radial migration and undergo close encounters with stars or compact objects, which has been shown in both analytical studies (e.g., Tagawa et al 2020;DeLaurentiis et al 2023), and hydrodynamics simulations (Li et al 2023;Rowan et al 2023aRowan et al , 2023bWhitehead et al 2023) to result in the formation of bound binaries. These binaries can be both retrograde and prograde and also both circular and eccentric, depending on the impact parameter of the encounter.…”
Section: Introductionmentioning
confidence: 97%
“…In an AGN disk, BHs are embedded due to capture via dynamical interactions between the nuclear star cluster and the AGN disk (Ostriker 1983;Miralda-Escudé & Kollmeier 2005;Wang et al 2024) and by in situ star formation (Levin & Beloborodov 2003;Goodman & Tan 2004;Milosavljević & Loeb 2004;Chen et al 2023b;Derdzinski & Mayer 2023). The AGN disk environment helps to bring the BHs closer together (Bellovary et al 2016;Derdzinski et al 2019Derdzinski et al , 2021Tagawa et al 2020b;Li et al 2021;Grishin et al 2023) and hence form binaries (Li et al 2022(Li et al , 2023Boekholt et al 2023;DeLaurentiis et al 2023;Qian et al 2024;Rowan et al 2023Rowan et al , 2024Rozner et al 2023;Whitehead et al 2023a;Whitehead et al 2023b), which then merge over relatively short timescales. Comparisons to the observed BH masses, spins, and merger rate indicate that a sizable fraction of the observed mergers may indeed originate in AGN disks (Tagawa et al 2021a;Gayathri et al 2021;Ford & McKernan 2022).…”
Section: Introductionmentioning
confidence: 99%